2010
DOI: 10.1016/j.fct.2010.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, cell cycle arrest, and apoptosis in breast cancer cell lines exposed to an extract of the seed kernel of Mangifera pajang (bambangan)

Abstract: An extract of Mangifera pajang kernel has been previously found to contain a high content of antioxidant phytochemicals. The present research was conducted to investigate the anticancer potential of this kernel extract. The results showed that the kernel crude extract induced cytotoxicity in MCF-7 (hormone-dependent breast cancer) cells and MDA-MB-231 (non-hormone dependent breast cancer) cells with IC50 values of 23 and 30.5 microg/ml, respectively. The kernel extract induced cell cycle arrest in MCF-7 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…Polyphenols phytochemicals are non-nutrient compound of plants that have been suggested to prevent and treat cardiovascular diseases, cancers, osteoporosis, neurodegenerative diseases and diabetes mellitus (Abu Bakar et al 2010). Phenolic acids and flavonoids which are most abundant in human diets are the examples of main classes of polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols phytochemicals are non-nutrient compound of plants that have been suggested to prevent and treat cardiovascular diseases, cancers, osteoporosis, neurodegenerative diseases and diabetes mellitus (Abu Bakar et al 2010). Phenolic acids and flavonoids which are most abundant in human diets are the examples of main classes of polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…The MTT assay is a common practice for studying the action of natural products on cell viability, proliferation and cytotoxicity. This assay is based on reduction of tetrazolium salt to a purple insoluble formazan by metabolically active cells [1]. The absorbance of the solubilized formazan is taken as a measure of the number of living cells.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, there is continuous search for new chemotherapeutic drugs by scientific exploitation of the enormous pool of naturally occurring chemicals [1]. The induction of cell death in cancer cells is an ideal strategy for cancer chemotherapy, and the use of agents with this capability has enticed interest in recent years [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that stem bark and leaf extracts from M. indica exhibit a wide range of pharmacological effects such as antioxidant, anticancer, antimicrobial, antiatherosclerotic, antiallergenic, anti-inflammatory, analgesic and immunomodulatory among many others; however, the underlying mechanisms involved in these effects are mostly not yet well described [Sanchez et al 2000;Beltran et al 2004;Engels et al 2009;Abu Bakar et al 2010;Ajila et al 2010;Chieli et al 2010;Kanwal et al 2010;Agarwala et al 2012]. In our investigations we studied the possible effects of M. indica as an antihypertensive drug.…”
Section: Discussionmentioning
confidence: 99%